HPA-axis multilocus genetic profile score moderates the association between maternal prenatal perceived stress and offspring depression in early adulthood. (February 2021) - McKenna, Brooke G.; Hammen, Constance; Brennan, Patricia A.
Abstract: Maternal stress during pregnancy can cause alterations to the fetal hypothalamus–pituitary–adrenal (HPA) axis, a phenomenon known as fetal programming that may have lasting effects on offspring outcomes, including depression. Evidence suggests that these effects may vary with respect to the offspring's genetic risk. Nonetheless, few studies have examined these effects into adulthood, when risk for depression onset is highest. The present study builds upon the extant literature by examining the interaction of maternal prenatal perceived stress (MPPS) and offspring HPA-axis polygenic risk to predict offspring depression in early adulthood. A total of 381 mother–child dyads participated in a prospective, longitudinal study that spanned from pregnancy until offspring were 20 years of age. Polygenic risk was defined by a multilocus genetic profile score (MGPS) that reflected the additive risk of three HPA-axis candidate genes. The results indicated that the interaction of MPPS and HPA-axis MGPS confers risk for offspring depression at age 20, in line with the differential susceptibility model. This interaction may be specific to prenatal stress, as maternal stress during early childhood did not interact with genetic risk to predict depression. These findings provide the first evidence that genetic variants that are associated with the HPA axis may act in a polygenic, additive fashion to moderate the association between fetal programming and adult depression.